Unveiling conserved HIV-1 open reading frames encoding T cell antigens using ribosome profiling - Lisa Bertrand; Annika Nelde; Bertha Cecilia Ramirez; Isabelle Hatin; Hugo Arbes; Pauline François; Stéphane Demais; Emmanuel Labaronne; Didier Decimo; Laura Guiguettaz; Sylvie Grégoire; Anne Bet; et al. (Nature Communications)
Abstract The development of ribosomal profiling (Riboseq) revealed the immense coding capacity of human and viral genomes. Here, we used Riboseq to delineate the translatome of HIV-1 in infected CD4+ T cells. In addition to canonical viral protein coding sequences (CDSs), we identify 98 alternative open reading frames (ARFs), corresponding to small Open Reading Frames (sORFs) that are distributed across the HIV genome including the UTR regions. Using a database of HIV genomes, we observe that most ARF amino-acid sequences are likely conserved among clade B and C of HIV-1, with 8 ARF-encoded amino-acid sequences being more conserved than the overlapping CDSs. Using T cell-based assays and mass spectrometry-based immunopeptidomics, we demonstrate that ARFs encode viral polypeptides. In the blood of people living with HIV, ARF-derived peptides elicit potent poly-functional T cell responses mediated by both CD4+ and CD8+ T cells. Our discovery expands the list of conserved viral polypeptides that are targets for vaccination strategies and might reveal the existence of viral microproteins or pseudogenes.